The price of our values: The economic limits of moral life - Landier, Augustin; Thesmar, David (Chicago Chicago University Press, 2025)
Modern life is an exercise in discomfort. In the face of endless injustice, how much selfishness is permissible? How do we square suffering elsewhere with our hope to thrive at home? How does one strive for the greater good while guarding one$1 (Bs personal interests? The Price of Our Values argues that the answers to these questions are economic: by weighing our sense of the personal costs associated with the outer limits of our moral beliefs.s